Freedom of the High Seas and Struggle against Terrorism (Summary) - E. S. Anyanova; V. N. Kulebiakin (Московский журнал международного права, 2013)
The article deals with the problem of illegal transportations of weapons of mass distraction (WMD) in the high seas. The basic principal of the international maritime law – freedom of the high seas – provides in particular for freedom of navigation. However freedom of navigation may contradict to the necessity of prevention of illegal transportation of WMD by the terrorist groups, which is deemed to be a part of the international “War on terrorism”. Measures of suppression of the illegal transportation of WMD are carried out in frames of the Proliferation Security Initiative (PSI) and the 2005 Protocols to the 1988 Convention for the Suppression of Unlawful Acts against the Safety of Maritime Navigation (SUA Convention) and the 1988 Protocol for the Suppression of Unlawful Acts against the Safety of Fixed Platform Located on the Continental Shelf (SUA Protocol). At present the PSI is regulated by means of the bilateral agreements, which are fulfilled by the signatory states.